Implementation of the Marriage Management Information System (SIMKAH) in Marriage Services at the Religious Affairs Office, Batudaa Pantai District, Gorontalo Regency - Maimum Udin Latibu; Sofyan Alhadar; Sabriana Oktaviana Gintulangi (Formosa Journal of Applied Sciences, 2023)
This research aims to determine the implementation of the Marriage Management Information System in Marriage Services at the Religious Affairs Office, Batudaa Pantai District, Gorontalo Regency. The data collection techniques used are: Observation, Interview and Secondary data recording techniques. In accordance with the type of research used, the data analysis technique used is qualitative analysis technique. The results of the research show that seen from the communication aspect, the number/human resources of officers and the preparation of plans are not yet effective or do not support the implementation of the Marriage Management Information System in Marriage Services at the Religious Affairs Office, Batudaa Pantai District, Gorontalo Regency. The things suggested in this research are the need for intensive communication between leaders and subordinates in carrying out work, the number of officers being increased and HR officers' abilities being increased and the preparation of plans maximized.